1998
DOI: 10.1002/(sici)1097-0274(199810)34:4<305::aid-ajim2>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of occupational lung disease in a random sample of former mineworkers, Libode district, Eastern Cape Province, South Africa

Abstract: Background Gold mineworkers in South Africa are exposed to high levels of silica dust as a result of which they are at risk of developing silicosis, which is a compensable disease. The incidence of tuberculosis is also high. Methods To determine the prevalence of occupational lung disease and the previous compensation history in former migrant mineworkers, a study was undertaken in a random sample of men living in Libode, a rural district of Eastern Cape Province, South Africa. Two hundred thirty‐eight ex‐mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 10 publications
2
26
2
Order By: Relevance
“…This population of former mineworkers was effectively hidden from view until two rural studies in the late 1990s, one in the Transkei region of South Africa and the other in Botswana, revealed the high prevalence of silicosis and associated tuberculosis in former mineworkers [Steen et al, 1997;Trapido et al, 1998a]. Based on these local prevalences, on the actual number of compensation awards for pneumoconiosis between 1973 and 1997, and on some educated guess work about the number of living mineworkers throughout Southern Africa, Trapido et al [1998b] estimated a liability of unpaid silicosis compensation of R9.96 billion in 1998.…”
Section: Funding and Compensation Paymentsmentioning
confidence: 99%
See 2 more Smart Citations
“…This population of former mineworkers was effectively hidden from view until two rural studies in the late 1990s, one in the Transkei region of South Africa and the other in Botswana, revealed the high prevalence of silicosis and associated tuberculosis in former mineworkers [Steen et al, 1997;Trapido et al, 1998a]. Based on these local prevalences, on the actual number of compensation awards for pneumoconiosis between 1973 and 1997, and on some educated guess work about the number of living mineworkers throughout Southern Africa, Trapido et al [1998b] estimated a liability of unpaid silicosis compensation of R9.96 billion in 1998.…”
Section: Funding and Compensation Paymentsmentioning
confidence: 99%
“…Some insight into the numerous barriers facing claimants comes from a survey of ex-miners in the Transkei region which implicated factors such as incorrect transcription of addresses, poor postal services in rural areas, low literacy among miners and their families, and limited banking services [Trapido, 1999]. A study of claims based on autopsy certification found that the majority of qualifying families did not respond to requests from the paying agency for further documentation, suggesting that the family did not receive the letter of certification, did not understand the procedure, or were unable to follow it [Murray et al, 2002].…”
Section: Barriers To Accessing Compensationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Occupational Disease in Mines and Works Act of 1973 requires mines to compensate current and ex-miners for a variety of occupational diseases, including TB. Yet several studies have shown the difficulties former miners face in accessing this compensation [5][6][7][8]. Trapido and colleagues quantified the prevalence of lung disease and compensation among former mine workers living in one rural South African district, and found that 24% of study participants were eligible for compensation but only 2.5% of those eligible had been paid in full and were entitled to no additional compensation [5].…”
Section: Compensation: New Laws and Enforcement Of Existing Lawmentioning
confidence: 99%
“…[6]. Functional ventilatory impairments in different groups of dust exposed workers and in patients with late forms of silicosis, and individuals with conventional silicosis and silicotuberculosis were studied by E. Petrova [2,7,8,9,10,11]. After a long monitoring of coal dust exposed workers without progressive massive fibrosis (PMF), R.S.…”
Section: Introductionmentioning
confidence: 99%